IP6 reduces colorectal cancer metastasis by mediating the interaction of gut microbiota with host genes - Lan, Tong-Tong; Song, Yang; Liu, Xiao-Han; Liu, Cui-Ping; Zhao, Hui-Chao; Han, Yi-Sa; Wang, Chu-Hui; Yang, Ning; Xu, Zhen; Tao, Meng; Li, Hui (Frontiers in Nutrition, 2022)
Inositol hexaphosphate (IP6) is a phytochemical widely found in grains and legumes that plays an anti-cancer role. However, the mechanism underlying the inhibition of colorectal cancer metastasis by IP6 through host genes, gut microbiota, and their interactions remain elusive. In this study, 16S rRNA sequencing was used to study the effect of IP6 on gut microbiota in an orthotopic transplantation model of colorectal cancer mice. The transcriptome was used to study the changes of host genes in metastasis and the relationship with gut microbiota. The results showed that the gut microbiota composition of model mice was significantly different from that of normal mice. The beta diversity partly tended to return to the normal level after IP6 intervention. Especially, Lactobacillus helveticus and Lactococcus lactis were recovered after IP6-treated. Enrichment analysis showed that the enrichment score of the Cytokine-Cytokine receptor interaction signal pathway decreased after IP6 treatment compared to the model group. Further analysis of differentially expressed genes (DEGs) in this pathway showed that IP6 reduced the expression of the Tnfrsf1b gene related to the area of liver metastasis, and the Tnfrsf1b gene was negatively correlated with the relative abundance of Lactobacillus helveticus. Our results presented that host gene, microbiome and their interaction may serve as promising targets for the mechanism of IP6 intervention in colorectal cancer metastasis.